2017
DOI: 10.1016/j.wjorl.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and minimally‐invasive ear surgery: A path to better outcomes

Abstract: The development of endoscopic ear surgery techniques promises to change the way we approach ear surgery. In this review paper, we explore the current evidence, seek to determine the advantages of endoscopic ear surgery, and see if these advantages are both measureable and meaningful. The wide field of view of the endoscope allows the surgeon to better visualize the various recesses of the middle ear cleft. Endoscopes make it possible to address the target pathology transcanal, while minimizing dissection or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Now the endoscopes have become the modern way of visualization in the surgical domain [19]. Recent studies on endoscopic stapes surgeries and outcomes have reported excellent audiological success rates [15,18]. All patients in the current study underwent conventional microscopic middle ear surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Now the endoscopes have become the modern way of visualization in the surgical domain [19]. Recent studies on endoscopic stapes surgeries and outcomes have reported excellent audiological success rates [15,18]. All patients in the current study underwent conventional microscopic middle ear surgery.…”
Section: Discussionmentioning
confidence: 93%
“…The microscope is the conventional method used for middle ear surgeries, and the endoscope has been recently utilized as an alternative technique to view middle ear structures [15,16]. A microscope allows binocular vision and freedom of both hands with an unobstructed direct view of the operating field [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the surgical approach, the use of endoscopes exclusively or as an adjunct to the microscope permits the surgeons to greatly enhance the visualization of the target pathology and landmarks. [ 12 ] The laser-assisted tympanostomy is ideal for patients with a narrow ECA. With the laser beam, a high-precision tympanostomy can be performed very easily, giving a good visualization of the middle-ear cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Wullstein used "ototypanoscope" from the company Storz with a diameter of 2,7 mm intraoperatively in 1984. In recent years 3 mm diameter oto-endoscopes are preferred to obtain better image quality [14] . In the current study, the smaller (2.7 mm diameter x 140 mm length) oto-endoscope was used without any problems in the paediatric age group.…”
Section: Discussionmentioning
confidence: 99%